2021
DOI: 10.1111/ina.12823
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory performance of humans exposed to moderate levels of carbon dioxide

Abstract: In a business-as-usual scenario, atmospheric carbon dioxide concentration (CO2) could reach 950 parts per million (ppm) by 2100. Indoor CO2 concentrations will rise consequently, given its dependence on atmospheric CO2 levels. If buildings are ventilated following current standards in 2100, indoor CO2 concentration could be over 1,300 ppm, depending on specific ventilation codes. Such exposure to CO2 could have physiological and psychological effects on building occupants. We conducted a randomized, within-sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Probably, the respiratory pattern of subjects during sleep did not change between conditions in the present study. Previous studies of subjects who were awake have documented reduced respiration in a polluted environment 52,53 and at high temperature 54 . Further studies are required to monitor the respiratory pattern during sleep at different temperatures and levels of IAQ.…”
Section: Discussionmentioning
confidence: 98%
“…Probably, the respiratory pattern of subjects during sleep did not change between conditions in the present study. Previous studies of subjects who were awake have documented reduced respiration in a polluted environment 52,53 and at high temperature 54 . Further studies are required to monitor the respiratory pattern during sleep at different temperatures and levels of IAQ.…”
Section: Discussionmentioning
confidence: 98%
“…As heart rate and minute ventilation are strongly correlated, 24 they inferred that changes in respiration rate and tidal volume could have affected ETCO 2 but the former did not change and the latter was not measured. Moreover, Mishra et al 20 showed that ETCO 2 and respiration rate did not differ significantly across three exposure conditions of CO 2 with bioeffluent: 900 ppm, 1,450 ppm (increase caused by reduced ventilation rate), and 1,450 ppm (pure CO 2 added, ventilation rate same as 900 ppm), although Forced Expiratory Volume flow in 1 second (FEV1) and Forced Vital Capacity (FVC) decreased with reduced ventilation. The studies mentioned above suggest that increased air pollution caused by increasing the levels of CO 2 , bioeffluents, or other pollutants to the levels that are typically observed indoors may reduce the rate of elimination of CO 2 from the lungs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in spirometry tests under different exposure conditions, Shriram et al 19 suggested that the exposure to high levels of CO2 and bioeffluents that is associated with low ventilation levels may reduce lung capacity. Additionally, Mishra et al 20 showed that exposure to bioeffluents but not CO 2 can affect pulmonary function.…”
Section: Introductionmentioning
confidence: 99%
“…As the level of CO 2 increases, the level of indoor contaminants may also be increasing. Recent studies have shown that the health effects associated with elevated CO 2 levels are varied and may be associated with other factors [Fisk et al 2019;Mishra et al 2021;Persily and de Jonge 2017].…”
Section: Carbon Dioxidementioning
confidence: 99%